LEGAL PROTECTION FOR FOREIGN LEGAL SUBJECTS IN INTERNATIONAL CONTRACTS: AN INTERNATIONAL PRIVATE LAW PERSPECTIVE - I Putu Dwika Ariestu; I Dewa Gede Herman Yudiawan; Putu Riski Ananda Kusuma (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2023)
The protection of foreign legal subjects in the context of international contracts has become an increasingly important issue in international relations. In the era of globalization and economic integration, international contracts serve as a primary instrument in facilitating cross-border transactions. However, foreign legal subjects face different challenges and risks compared to domestic legal subjects. This journal examines the legal protection of foreign legal subjects in international contracts from the perspective of international private law. International private law plays a crucial role in governing legal relationships between nations and resolving disputes involving foreign legal subjects. Foreign legal subjects, such as individuals, companies, or legal entities from other countries, require effective legal protection in contractual rights, enforcement of intellectual property rights, dispute resolution, and prevention of discrimination. Challenges include differences in laws between nations, variations in the understanding of principles of international private law, and disparities in jurisdictional systems. To provide fair and equal legal protection for foreign legal subjects, it is important to understand the perspective of international private law. This journal analyzes various aspects of legal protection for foreign legal subjects in international contracts through a doctrinal approach and analysis of international court practices. The analysis and findings of this journal are expected to contribute to the understanding of the legal protection of foreign legal subjects in the context of international contracts and promote the development of more effective and inclusive legal frameworks.